Ideal Free Distribution in Two Patches (Journal of Nonlinear Modeling and Analysis, 2024)
In this survey we discuss some recent progress on the ideal freedistribution theory in patch models, with the emphasis on two patches. Weshow that dispersal strategies leading to the ideal free distributions of organisms are generally evolutionarily stable. We will also study the existence ofevolutionarily stable dispersal strategies when dispersal strategies do not leadto the ideal free distributions. Applications to some river models are given.